Spectroscopic and Biological Studies of Phenanthroline Compounds: Selective Recognition of Gene‐Promoter G‐Quadruplex DNAs Preferred over Duplex DNA. Issue 6 (18th June 2013) - Wang, Lihua; Wei, Chunying
Abstract G‐Quadruplex DNA formed in the promoter regions of proto‐oncogenes would block the transcription process and eventually suppress the development of tumors, so compounds that stabilize G‐quadruplex DNA are potential antitumor drugs. This article describes the interactions of three phenanthroline compounds, a–c, with proto‐oncogene c‐kit2 and c‐myc G‐quadruplex DNAs by means of polymerase chain reaction (PCR) stop assay, fluorescence resonance energy transfer melting (FRET melting) assay, fluorescence indicator displacement (FID) assay, UV/VIS absorption, fluorescence, and circular dichroism (CD) spectroscopies. All three compounds displayed selectivity for the G‐quadruplex over duplex, with binding constants (Ka) for the both quadruplexes varying from 0.49×106 to 3.32×106 M−1 (4.1‐ to 33.2‐fold specificity). Compounds a, b, and c were potential stabilizers for the c‐kit2 G‐quadruplex with the melting‐temperature increase (ΔTm) values of 12–15°. CD Spectra indicated that a–c disrupted the structure of c‐kit2 G‐quadruplex, whereas no significant change was observed for c‐myc G‐quadruplex.